Determinants of human milk oligosaccharides profiles of participants in the STRONG kids 2 cohort - Fan, Yuting; Vinjamuri, Anita; Tu, Diane; Lebrilla, Carlito B.; Donovan, Sharon M. (Frontiers in Nutrition, 2023)
Human milk oligosaccharides (HMOS) are indigestible carbohydrates that support infant development by establishing a healthy microbiota, preventing infectious diseases, and promoting immune and cognitive development. Individual HMOS have distinct functions based on their chemical structures. HMO profiles can vary largely among mothers, but the research on factors other than genetic background affecting HMO composition are limited. In the present analysis, we examined the relationships between maternal characteristics and the HMO profiles of breastfeeding mothers (n=392) in the STRONG kids 2 with the following demographic characteristics: average age: 30.8 y, 76.8% White, and 75.5% exclusively breastfeeding. Human milk samples were collected at 6 weeks postpartum and maternal information was obtained from self-reported surveys. Information on dietary intake changes since the participants have been breastfeeding was collected. HMO profiles were analyzed by high performance liquid chromatography coupled with mass spectrometry and secretor status was determined by the presence of four secretor markers (2′-fucosyllactose [2′-FL], LNFP I, LDFT, and TFLNH). Spearmen correlation test was utilized to determine the relationships between individual HMOS and associations with maternal factors. Between-group differences in HMO relative abundances were examined with Kruskal-Wallis test. Among all participants, 71.9% were secretors and 28.1% were non-secretors. The relative abundances of all HMOS differed (p<0.05) by secretor status, with the exception for 6′-SL and 3′-SL. Positive correlations were observed among HMOS with similar structures, such as the 𝛼1,2-fucosylated HMOS. The abundances of select HMOS were associated with maternal body weight, pregnancy complications, and dietary characteristics. Based on pre-pregnancy BMI, in all mothers, the relative abundance of 3′-SL was significantly higher in overweight mothers than obese mothers (p=0.013). In milk produced by non-secretor mothers, LNPF I+III abundances were greater in overweight than normal weight mothers (p=0.020). Several HMO abundances were found to be associated with Gestational diabetes mellitus (GDM). Variations of HMO abundances were also observed with dietary food intake. In all mothers, egg consumption was positively correlated with LNT+LNnT (p=0.012) and cheese intake was positively associated with 2′-FL and S-LNnH II abundances (p=0.046 and 0.026, respectively). Future research will investigate associations between HMOS and maternal and infant outcomes.